Textbook of Rapid Response Systems : Concept and Implementation - DeVita, Michael A.; Hillman, Ken; Bellomo, Rinaldo; Odell, Mandy; Jones, Daryl A.; Winters, Bradford D.; Lighthall, Geoffrey K. (Springer International Publishing : Imprint: Springer, 2017)
The latest edition of this text is the go-to book on rapid response systems (RRS). Thoroughly updated to incorporate current principles and practice of RRS, the text covers topics such as the logistics of creating an RRS, patient safety, quality of care, evaluating program results, and engaging in systems research. Edited and written by internationally recognized experts and innovators in the field, Textbook of Rapid Response Systems: Concepts and Implementation, Second Edition is a valuable resource for medical practitioners and hospital administrators who want to implement and improve a rapid response system.
Keywords: Medicine.; Anesthesiology.; Emergency medicine.; Critical care medicine.; Cardiology.; elektronické knihy; electronic books